Sources of competitive advantages and business performance - Strandskov, Jesper (Journal of Business Economics and Management, 2006)
Based on data from the European meat processing industry three sets of competitive sources on business performance are studied: Firm Specific Advantages (FSAs), Localizational Specific Advantages (LSAs) and Relation Specific Advantages (RSAs). The results indicate that the FSAs and the RSAs are the most important explanatory variables on business performance, however, with strong interaction effects between the two sets of variables. Given the findings, we call for further empirical validation of how the different sets of competitive advantages interact and reinforce each. A closer examination of the nature of the RSAs, ie resource accumulation and development through inter‐firm co‐operation is also needed.Firstd Published Online: 14 Oct 2010